2017
DOI: 10.1556/1886.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and clinical outcome of HIV-related tuberculosis in a population of TB patients in South-Western Nigeria

Abstract: Tuberculosis (TB) is the second leading cause of death from infectious disease globally with its impact more dramatic in resource limited settings. Individuals with human immunodeficiency virus (HIV) infection who also develop tuberculosis represent a significant challenge to TB control. This study was carried out to determine the prevalence of TB–HIV coinfection and pattern of infection among TB patients. We also compared treatment outcome among coinfected patients with those not coinfected.A six-year retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…[10,12] In this study pulmonary tuberculosis was predominantly (66.99%) found in HIV-TB infected cases. This is consistent with fi ndings reported by Chandra et al (60.58%), Kamath et al (60.20%) and Olowe et al (94.30℅) [12,16,17] but contrasting results have been found in studies conducted by Dahiya et al, Chandra et al and Kavya et al [10,12,15] with higher incidence of extra-pulmonary TB than pulmonary TB among HIV-TB co-infected patients. A higher percentage of patients with HIV-PTB (32.38%) were observed to have CD4 cell count less than 200 cells/µL as compared to HIV-EPTB (30.90%).…”
Section: Resultssupporting
confidence: 90%
“…[10,12] In this study pulmonary tuberculosis was predominantly (66.99%) found in HIV-TB infected cases. This is consistent with fi ndings reported by Chandra et al (60.58%), Kamath et al (60.20%) and Olowe et al (94.30℅) [12,16,17] but contrasting results have been found in studies conducted by Dahiya et al, Chandra et al and Kavya et al [10,12,15] with higher incidence of extra-pulmonary TB than pulmonary TB among HIV-TB co-infected patients. A higher percentage of patients with HIV-PTB (32.38%) were observed to have CD4 cell count less than 200 cells/µL as compared to HIV-EPTB (30.90%).…”
Section: Resultssupporting
confidence: 90%
“…22,24 The current study revealed that the highest prevalence of HIV positivity was among pulmonary TB (25; 61%). This result is consistent with findings reported by Chandra et al, 35 Kamath et al, 18 and Olowe et al 36 where higher seropositivity of HIV were detected in cases of pulmonary TB. In addition, a study by Jha et al 37 from eastern Nepal showed that 71.4% of the TB/HIV co-infected cases were suffering more commonly from pulmonary TB than with extra-pulmonary TB (28.6%).…”
Section: Discussionsupporting
confidence: 93%
“…3,4 Previous studies have contributed fundamental knowledge to TB prevention strategies by identifying key TB characteristics for HIV-seropositive and -seronegative patients in some populations. [5][6][7][8] Such knowledge is important, as failure to receive antiretroviral therapy for HIV infection in TB patients is known to be a risk factor for poor health outcomes of TB/HIV-coinfected patients. 9 With a better understanding of how TB disease disseminates throughout the body of people living with and without HIV, clinicians are able to make timely, accurate diagnosis of the disease.…”
Section: Introductionmentioning
confidence: 99%